PERSPEKTIF MAHASISWA TEKNIK K3 PPNS TENTANG DAMPAK PENGGUNAAN GADGET TERHADAP KUALITAS KEHIDUPAN SOSIAL DAN AKADEMIK - Kharisma Innayatul Zulfa; Rhino Aryo Wicaksono; Muhammad Rafli Al Thariq; Denny Oktavina Radianto (Universitas Pahlawan Tuanku Tambusai, 2023)
The Use of Gadgets Within the scope of Occupational Safety and Health Engineering Students of the Surabaya State Shipping Polytechnic are often used to access and learn E-Learning provided by the campus. Students can access E-Learning anytime and anywhere. The use of E-Learning is used from the time of the COVID-19 outbreak until now. But at this time the learning system applied by the Surabaya State Shipping Polytechnic is Hybrid with Online and Offline. Therefore, gadgets are very attached to student life. This research was conducted to find out how the quality of social and academic life of students in this digitalization era. Our research uses a qualitative approach method by distributing online questionnaires to Occupational Safety and Health Engineering Students class of 2019 – 2022. From the questionnaires that have been distributed, it can be known the impact of using gadgets for students. The positive impact of the existence of gadgets in academic terms is that respondents can find information and references regarding lecture assignments. In addition, respondents can also find new things that are not taught in lectures. Meanwhile, the negative impact of the existence of gadgets in academic terms is that they become lazy to study when they play gadgets. In addition, according to respondents with the presence of gadgets can have an impact on the surrounding environment such as less care when spoken directly by the interlocutor, this is also related to our ethics in respecting the interlocutor. From these results, a wise attitude is needed in using gadgets in order to get benefits for students. Keywords: Gadget Impact, Students academic, social interaction